Representasi terhadap Perempuan Hamil di Luar Nikah dalam Novel Menjaring Mata Angin karya Triman Laksana: Representation of Unmarried Pregnant Women in the Novel Menjaring Mata Angin by Triman Laksana - Nadila, Sinta Maudy; Purnamasari, Hetty; Amrullah, Imron (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
This study aims to examine how unmarried pregnant women are portrayed in Triman Laksana’s novel Menjaring Mata Angin. The research applies Stuart Hall’s (1997) theory of representation and Tong’s (2004) liberal feminist theory. In Indonesian society, unmarried pregnant women are often perceived as violating social and religious norms, which leads to their being subjected to stigma and discrimination. This study seeks to fill a gap in previous research, which generally focuses on patriarchy in broad terms without highlighting more specific forms of representation. The method employed in this research is descriptive qualitative with a critical discourse analysis approach. The data consist of selected excerpts from the novel Menjaring Mata Angin, which were collected through close reading and subsequently verified using theoretical triangulation. The analysis centers on various forms of female representation, particularly in three aspects: physical-symbolic, socio-cultural, and ideological. The findings reveal that in the physical-symbolic aspect, the female body is depicted as a moral symbol constantly subjected to surveillance. In the socio-cultural aspect, women are portrayed as guardians of family honor. Meanwhile, in the ideological aspect, masculine control is evident in the restrictions placed on women’s bodily autonomy. However, the main character in the novel exhibits acts of resistance against this system, reflecting the spirit of liberal feminism, which emphasizes women’s freedom and autonomy. Based on these findings, it is concluded that Menjaring Mata Angin functions as a counter-discourse that not only reflects the social conditions faced by women but also critiques patriarchal ideology and gender injustice within Indonesian culture.